An in vivo Cell-Based Delivery Platform for Zinc Finger Artificial Transcription Factors in Pre-clinical Animal Models - Deng, Peter; Halmai, Julian A. N. M.; Beitnere, Ulrika; Cameron, David; Martinez, Michele L.; Lee, Charles C.; Waldo, Jennifer J.; Thongphanh, Krista; Adhikari, Anna; Copping, Nycole; Petkova, Stela P.; Lee, Ruth D.; et al. (Frontiers in Molecular Neuroscience, 2022)
Zinc finger (ZF), transcription activator-like effectors (TALE), and CRISPR/Cas9 therapies to regulate gene expression are becoming viable strategies to treat genetic disorders, although effective in vivo delivery systems for these proteins remain a major translational hurdle. We describe the use of a mesenchymal stem/stromal cell (MSC)-based delivery system for the secretion of a ZF protein (ZF-MSC) in transgenic mouse models and young rhesus monkeys. Secreted ZF protein from mouse ZF-MSC was detectable within the hippocampus 1 week following intracranial or cisterna magna (CM) injection. Secreted ZF activated the imprinted paternal Ube3a in a transgenic reporter mouse and ameliorated motor deficits in a Ube3a deletion Angelman Syndrome (AS) mouse. Intrathecally administered autologous rhesus MSCs were well-tolerated for 3 weeks following administration and secreted ZF protein was detectable within the cerebrospinal fluid (CSF), midbrain, and spinal cord. This approach is less invasive when compared to direct intracranial injection which requires a surgical procedure.